An Algorithm for Denoising Using Principle Component Analysis (PCA) Thresholding based Dual Tree Complex Wavelet Transform (DTCWT) and Block Matching Algorithm (BMA) On Ultrasound Medical Image (International Journal of Psychosocial Rehabilitation, 2020)
We suggest in this research a denoising methodology by using Dual Tree Complex Wavelet Transform (DTCWT) and Block Matching Algorithm (BMA), collectively known as DTCWT-BMA. DTCWT-BMA is a way of identifying the information of noisy pixels and increasing the image noise. In the beginning the noisy picture is provided as input. Then, produce the corresponding sections of images together into the stack. Complex Wavelet Transform (CWT) is then enforced on every element within the cluster. Then after, thresholding of the Principle Component Analysis (PCA) is implemented to improve the picture in which the de-noising outcome is visibly much greater. The picture with decomposition is composed of description and estimated coefficients. By choosing the right primary component and utilizing PCA, the entire description and estimation of coefficients is thresholded to exclude the neighboring associated wavelet coefficients. The reverse DTCWT is being used after thresholding the corresponding associated coefficients. Use PCA to extract the denoised image from the decomposition picture. Finally, you will attain an improved picture with decreased noise. A picture with noise could be extemporized in visual quality; it simply modifies the coefficients using a soft-thresholding technique. Additive, speckle, multiplicative, and Gaussian noises and their elements affect ultrasound pictures, which mitigate the picture quality and affect human comprehension. Therefore, using a PCA system based on DTCWT thresholding enables a significant reduction in the rate of noise for the US image provided. The research result indicates that the anticipated strategy offers enhanced outcomes in terms of maximum PSNR, SSIM and minimum MSE and execution time rather than the previous Fisz transformation and DWT methods